Key Aspects of Explication of Thinking in the Sergii Krymskyi's Legacy of the Soviet Period - Vitali Turenko; Nataliia Yarmolitska (International Society of Philosophy and Cosmology, 2019)
The article is devoted to the problem of thinking, which is one of the key issues of Sergii Krymskyi`s legacy. The paper observes the analysis of the Soviet scientific legacy of the thinker conducted in the field of history of philosophy. The paper focuses is on the scholar's philosophical writings, which had been published between the 60's-70 of the 20th century. Authors observe the period of formation of "Kiev school of the logic of scientific cognition" in the '60s. Sergii Krymskyi was one of the leaders of the mentioned school and, along with his associates, proved that scientific thought cannot be subordinated to any ideological dictate. It is claimed that despite the pressure of the Marxist-Leninist ideology in his early years the scholar did not leave his intention to explore the nature of logical laws in order to find a solution to the problem of the genesis of forms and laws of thought. Sergii Krymskyi, following the style of scientific thinking, looked for the prospects for developing this issue in various fields of knowledge.